Collaboration in Education Services for Children with Special Needs Inclusive School - Jaya, Indra; Maulidina, Citra Ashri; Kasirah, Irah; Taboer, Mohammad Arif; Bahrudin, Bahrudin; Yusro, Muhammad Najmil (Department of Special Education, 2023)
Based on the observations and explanations of special guidance teachers in schools, inclusive education providers that the form of collaboration between teachers and stakeholders is still diverse. In general, this study aims to find out and obtain information about the implementation of collaboration between teachers and stakeholders in education services for children with special needs in schools providing inclusive education in Sukabumi. This research is a quantitative research. Data collection techniques are carried out by distributing questionnaires and recording initial data in the form of records that are understood by researchers without reducing the actual data. The results of the study can be concluded that collaboration in several aspects is still lacking such as teacher collaboration with SLB, teacher collaboration with related experts, lack of teacher collaboration with resource centers, teachers are also still lacking collaboration in carrying out learning activities. Meanwhile, there are several aspects that have begun to develop well, including teacher collaboration with parents, as well as teacher collaboration with special guidance teachers in inclusive schools, although not yet dehydrated, maximum results are expected to be a reference in building good collaboration between teachers and related stakeholders in creating effective learning in inclusive education. This study illustrates that inclusive education in its implementation process requires support from teachers and related stakeholders in order to run optimally.